Zinc Electroplated Coating and Post Weld Heat Treatment on Micro Dissimilar Metal Inert Gas Welding - Mahrus Khoirul Umami,; Hakam Muzakki,; Zainal Arifin, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The welding process could reduce the performance of the material both microstructure and mechanical strength. Therefore, handling the welding results was necessary. There are several ways to improve the performance of welded joints, namely heat treatment and coating using electroplating. The materials used were galvanized and stainless steel 201 with a size of 100 x 50 x 0.5 mm. Welding used the Metal Inert Gas (MIG) method, while the filler metal used was AWS ER70S-6. The results of the welding were coated by electroplating, while the post-weld heat treatment was carried out to determine the effect of electroplating and heat treatment on the hardness of the joints. There were three temperature variations namely 250 °C, 300 °C, and 350 °C, and three variations of holding time, namely 30 minutes, 60 minutes, and 90 minutes. The highest value of roughness (116.68 VHN) was obtained from a combination of a temperature of 300 °C and a holding time of 30 minutes. While the lowest hardness value (54.93 HVN) was obtained from a temperature of 300 °C with a holding time of 90 minutes.